Relationships Between Sexting, Self-Esteem, and Sensation Seeking Among Australian Young Adults. (22nd April 2016) - Scholes-Balog, Kirsty; Francke, Nicole; Hemphill, Sheryl
The influence of information communication technology has brought about the phenomenon of sexting. Sexting is defined as sending, receiving, or forwarding on sexually explicit messages and images via the Internet or a mobile phone. The current study investigated relationships between sexting, sensation seeking, and self-esteem. Sexting was categorized in six ways: sending (1) sexually suggestive photos or videos, (2) photos or videos wearing lingerie, (3) nude photos or videos, (4) sexually suggestive text messages, (5) text messages propositioning sex, and (6) forwarding on or showing others sexts which were meant to be kept private. The sample comprised 583 young adults (80% female, M age = 20.72 years, SD age = 2.13) who participated in an online survey. The strongest predictor of sending all types of sexts was being in a relationship (compared to being single). In addition, high self-esteem was associated with reduced odds of sending nude photos/videos, while high sensation seeking was associated with increased odds of sending suggestive texts and texts propositioning sex. Finally, high self-esteem was associated with decreased odds, and high sensation seeking with increased odds, of forwarding on sexts which were meant to be kept private. This pattern of associations points to differences underlying engagement in the various types of sexting behaviors. Such information can be used by educators, parents, and clinicians to raise awareness of traits which make an individual more likely to engage in sexting, with a view to prevention and education about the risks of sexting and violation of privacy.